Development of a melt processing route for the fabrication of Tl-1223 coils - Moore, J; Hyland, D; Fox, S; Naylor, M; Wivell, S; Grovenor, C (1997)
Tl-1223 tapes with densities, (E-J(c)) values, of 2500Acm(-2) can be routinely fabricated but the magnetic field properties are poor due to weak link effects. We have developed a partial melt processing route which results in increased grain growth with greater potential for achieving grain alignment. We have investigated the effect of Tl-1223 phase composition on the melt process and found that Bi substitutions lead to an increased grain size in tapes made using unreacted powder but a decrease in grain growth in tapes made with reacted powder.